Single arm two‐stage studies: Improved designs for molecularly targeted agents. (15th August 2018) - Dutton, P.; Holmes, J.
Summary: Mechanistic understanding of cancers and their potential interactions with molecularly targeted agents is driving the need for stratified medicine to ensure each participant receives the best possible care. This understanding, backed by scientific research, should be used to guide the design of clinical trials for these agents. The mechanism of action of a molecularly targeted agent often suggests that a biomarker can be used as a predictor of activity of the agent on the targeted disease. A biomarker driven trial is needed to confirm that the molecularly targeted agent stratifies the participant population with disease into high and low responder groups. We assume that the biomarker of interest can be dichotomised and propose a balanced parallel two‐stage single‐arm phase II trial that builds on existing two‐stage single‐arm designs. A single‐arm trial cannot distinguish between a marker being predictive in the population as a whole and the agent causing an increased response in the marker positive group, but it is a first step. We compare this approach to the existing single‐arm approaches, sequential enrichment, tandem two‐stage, and parallel two‐stage designs, and discuss the advantages and disadvantages of each design. We show that our design compares favourably to existing designs in the Bayesian framework, making a more efficient use of collected data. We recommend using the parallel two‐stage balanced or sequential enrichment designs when randomisation is not practical in a phase II trial.